Observational Study of the Associations of Participation in High School Football With Self-Rated Health, Obesity, and Pain in Adulthood. Issue 6 (29th November 2019) - Gaulton, Timothy G; Deshpande, Sameer K; Small, Dylan S; Neuman, Mark D
Abstract: American football is the most popular high school sport in the United States, yet its association with health in adulthood has not been widely studied. We investigated the association between high school football and self-rated health, obesity, and pain in adulthood in a retrospective cohort study of data from the Wisconsin Longitudinal Study (1957–2004). We matched 925 males who played varsity football in high school with 1, 521 males who did not play football. After matching, playing football was not associated with poor or fair self-rated health (odds ratio (OR) = 0.88, 95% confidence interval (CI): 0.63, 1.24; P = 0.48) or pain that limited activities (OR = 0.86, 95% CI: 0.59, 1.25; P = 0.42) at age 65 years. Football was associated with obesity (body mass index (weight (kg)height (m) 2 ) ≥30) in adulthood (OR = 1.32, 95% CI: 1.06, 1.64; P = 0.01). The findings suggest that playing football in high school was not significantly associated with poor or fair self-related health at age 65 years, but it was associated with the risk of being obese as an adult in comparison with not playing football in high school. Our findings provide needed information about the risk of playing football with regard to a broader set of health outcomes.